Genetic Diversity and Species Identification of Unhatched Sea Turtle Eggs from Southern Bali Hatcheries - Dewana, I Gede Jose; Pertiwi, Ni Putu Dian; Yuliastuti, Yuliastuti; Yusmalinda, Ni Luh Astria; Luh Putu Candra Apriliani; Savitri, Ni Komang Rossa Sri; Rachmawati, Rita; Sembiring, Andrianus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Genetic data of sea turtles in Southern Bali remains limited as most previous studies rely on adult or live samples, while unhatched eggs are rarely utilized as a genetic resource. This study aims to identify the species and genetic diversity of unhatched sea turtle eggs from conservation sites in Southern Bali using mitochondrial control region. A total of six non-viable eggs were analyzed through DNA extraction, PCR, sequencing, and data analysis using MEGA 11, NCBI BLAST, and DnaSP v6. The identification results revealed that all samples belonged to the species of Lepidochelys olivacea (olive ridley turtle), with sequence similarity ranging from 99.54% to 100% and query coverage of 89% to 99% compared to reference data from GenBank. Phylogenetic analysis showed that all samples clustered within the same clade, with intraspecific genetic distances ranging from 0 to 0.008. Genetic diversity analysis revealed a haplotype diversity (Hd) of 0.86667 and nucleotide diversity (π) of 0.00306, with a total of four distinct haplotypes and six polymorphic sites. These findings indicate that unhatched sea turtle eggs still contain viable genetic material for analysis and suggest that Lepidochelys olivacea is the dominant nesting species found in Southern Bali. This study carries important implications for advancing conservation policy, enhancing habitat protection, minimizing inbreeding risks, and strengthening the use of species identification through forensic genetics.